Network Topology of Biological Aging and Geroscience-Guided Approaches to COVID-19 - Landay, Alan; Bartley, Jenna M.; Banerjee, Dishary; Hargis, Geneva; Haynes, Laura; Keshavarzian, Ali; Kuo, Chia-Ling; Kwon, Oh Sung; Li, Sheng; Li, Shuzhao; Oh, Julia; Ozbolat, Ibrahim Tarik; et al. (Frontiers in Aging, 2021)
Aging has emerged as the greatest and most prevalent risk factor for the development of severe COVID-19 infection and death following exposure to the SARS-CoV-2 virus. The presence of multiple co-existing chronic diseases and conditions of aging further enhances this risk. Biological aging not only enhances the risk of chronic diseases, but the presence of such conditions further accelerates varied biological processes or “hallmarks” implicated in aging. Given growing evidence that it is possible to slow the rate of many biological aging processes using pharmacological compounds has led to the proposal that such geroscience-guided interventions may help enhance immune resilience and improve outcomes in the face of SARS-CoV-2 infection. Our review of the literature indicates that most, if not all, hallmarks of aging may contribute to the enhanced COVID-19 vulnerability seen in frail older adults. Moreover, varied biological mechanisms implicated in aging do not function in isolation from each other, and exhibit intricate effects on each other. With all of these considerations in mind, we highlight limitations of current strategies mostly focused on individual single mechanisms, and we propose an approach which is far more multidisciplinary and systems-based emphasizing network topology of biological aging and geroscience-guided approaches to COVID-19.